Analisis Prinsip Pertanggungjawaban Pidana Individu: Mungkinkah Xi-Jinping Bertanggung Jawab ? - Rifqi Daffa Saputra; Dwi Putri Lestarika; Wevy Efticah Sary (GLOBAL SCIENTS PUBLISHER, 2025)
Humanitarian crimes against Uyghur Muslims in Xinjiang China have drawn increasing attention from around the world. This study aims to examine the regulation of individual criminal responsibility according to the 1998 Rome Statute and the possibility of Xi Jinping being punished for the persecution of Uighur Muslims. This study is a normative law study with a literature study to collect data. The data obtained is processed with a descriptive qualitative analysis method. The results of the study show that individual criminal responsibility for acts of persecution can be taken by the ICC if it fulfills the jurisdiction and flow stipulated in the Rome Statute in line with that Xi Jinping has the possibility of being punished for acts of persecution against Uighur Muslims based on complementarity jurisdiction.